Using a smartphone video camera to reduce anxiety in speaking activity - Nur Asma (Universitas Syiah Kuala, 2021)
The common problems faced by students in English speaking are anxiety and the lack of confidence and ideas. This research was conducted to determine the relevant factors and to provide a solution by using the smartphone video camera. To obtain the data in this research, experimental research was performed inside and outside the classroom with a series of treatments and a questionnaire sheet as the instrument. The data were analyzed using a model proposed by Smeda, Dakich, and Sharda (2014) and a Likert scale questionnaire, which was adapted from Spratt, Humphreys, and Chan (2002). The result from the test showed a significant difference between the experimental and control classes as the carried t-test presented the score of -8.36, which was out of the limit (between -1.96 and 1.96). Another result was the students developed positively which was shown by: the anxiety tends to decrease as they were given time before performing thus prepared better, their self-confidence was increased and challenged by using the smartphone video camera method due to the application of innovation in the speaking class. The conclusion of this research is lecturer needs to apply new methods, one of which is using a smartphone application.